A Tilted Axis: Maladaptive Inflammation and HPA Axis Dysfunction Contribute to Consequences of TBI - Tapp, Zoe M.; Godbout, Jonathan P.; Kokiko-Cochran, Olga N. (Frontiers in Neurology, 2019)
Each year approximately 1.7 million people sustain a traumatic brain injury (TBI) in the US alone. Associated with these head injuries is a high prevalence of neuropsychiatric symptoms including irritability, depression, and anxiety. Neuroinflammation, due in part to microglia, can worsen or even cause neuropsychiatric disorders after TBI. For example, mounting evidence demonstrates that microglia become “primed” or hyper-reactive with an exaggerated pro-inflammatory phenotype following multiple immune challenges. Microglial priming occurs after experimental TBI and correlates with the emergence of depressive-like behavior as well as cognitive dysfunction. Critically, immune challenges are various and include illness, aging, and stress. The collective influence of any combination of these immune challenges shapes the neuroimmune environment and the response to TBI. For example, stress reliably induces inflammation and could therefore be a gateway to altered neuropathology and behavioral decline following TBI. Given the increasing incidence of stress-related psychiatric disorders after TBI, the degree in which stress affects outcome is of particular interest. This review aims to highlight the role of the hypothalamic-pituitary-adrenal (HPA) axis as a key mediator of stress-immune pathway communication following TBI. We will first describe maladaptive neuroinflammation after TBI and how stress contributes to inflammation through both anti- and pro-inflammatory mechanisms. Clinical and experimental data describing HPA-axis dysfunction and consequences of altered stress responses after TBI will be discussed. Lastly, we will review common stress models used after TBI that could better elucidate the relationship between HPA axis dysfunction and maladaptive inflammation following TBI. Together, the studies described in this review suggest that HPA axis dysfunction after brain injury is prevalent and contributes to the dynamic nature of the neuroinflammatory response to brain injury. Experimental stressors that directly engage the HPA axis represent important areas for future research to better define the role of stress-immune pathways in mediating outcome following TBI.